A quantitative analysis of rust (Uromyces fabae) resistance in pea (Pisum sativum) using RILs - SINGH, A K; RAI, R; SRIVASTAVA, C P; SINGH, B D; KUSHWAHA, C; CHAND, R (The Indian Journal of Agricultural Sciences, 2012)
In a quantitative analysis of pea rust resistance using a RIL population, heritability estimates for disease severity and AUDPC were found to be 0.90 and 0.93, respectively. High heritability indicated that selection for pea rust resistance can be made under polyhouse conditions using either disease severity or AUDPC as disease reaction estimators. Average degree of dominance (ADD) for resistance to U. fabae was 0.11 and 0.14 for disease severity and AUDPC, respectively, indicating that the genes controlling U. fabae resistance exhibited a low degree of incomplete dominance. Estimates of the minimum number of effective genes conferring resistance to pea rust, using three different methods of estimation, varied from two to three.